Yoghurt containing galacto-oligosaccharides, prunes and linseed reduces the severity of mild constipation in elderly subjects - Sairanen, U; Piirainen, L; Nevala, R; Korpela, R (European journal of clinical nutrition, 2007)
Objective: Constipation is a common problem in the elderly. Dietary fibre is recommended for its treatment. The aim was to examine whether yoghurt containing galacto-oligosaccharides (GOS), prunes and linseed relieve constipation in elderly subjects. Design: A randomized, double-blinded, cross-over study. Setting: Free-living subjects. Subjects: A group of 43 elderly subjects with self-reported constipation (mean age 76 years, range 61-92 years, 32 females, 11 males). Interventions: The study consisted of a 2-week baseline period and 2, 3-week dietary interventions, with a 2-week wash-out period between the interventions. During the interventions, the subjects ingested, in random order, 260 g/day of either control yoghurt or test yoghurt containing GOS (12 g/day), prunes (12 g/day) and linseed (6 g/day). The use of laxatives was controlled and only allowed after 2 days without defecation. Results: Defecation frequency was 5.7 times/week during the baseline period. During the test yoghurt period, defecation frequency was higher (8.0 vs 7.1 times/week, P=0.011), defecation was easier (on the scale 0-3, 1.3 vs 1.5, P=0.010), and there was a tendency towards softer stools (on the scale 0-3, 2.1 vs 2.2, P=0.059) compared with the control yoghurt period. The subjects felt that the test yoghurt relieved constipation more effectively than the control yoghurt (P=0.005). The sum of gastrointestinal symptoms did not differ between the interventions. The use of laxatives remained constant throughout the study. Conclusions: Daily intake of yoghurt containing GOS, prunes and linseed reduced the severity of constipation in elderly subjects with mild constipation.